Prospective welfare analysis: Extending willingness-to-pay assessment to embrace sustainability - Roman Inderst; Stefan Thomas (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2022)
In this paper we outline how a future change in consumers' willingness-to-pay can be accounted for in a consumer welfare effects analysis in antitrust. Key to our solution is the prediction of preferences of new consumers and changing preferences of existing consumers in the future. The dimension of time is inextricably linked with that of sustainability. Taking into account the welfare of future cohorts of consumers, concerns for sustainability can therefore be integrated into the consumer welfare paradigm to a greater extent. As we argue in this paper, it is expedient to consider changes in consumers' willingness-to-pay, in particular if society undergoes profound changes in such preferences, e.g., caused by an increase in generally available information on environmental effects of consumption, and a rising societal awareness about how consumption can have irreversible impacts on the environment. We offer suggestions on how to conceptionalize and operationalize the projection of such consumers' changing preferences in a "prospective welfare analysis". This increases the scope of the consumer welfare paradigm and can help to solve conceptual issues regarding the integration of sustainability into antitrust enforcement while keeping consumer surplus as a quantitative gauge.
urn:nbn:de:hebis:30:3-616640
Keywords: A13; K21; K32; 330; Antitrust; Consumer Welfare; Sustainability